2003
DOI: 10.1056/nejmoa030660
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Finasteride on the Development of Prostate Cancer

Abstract: Finasteride prevents or delays the appearance of prostate cancer, but this possible benefit and a reduced risk of urinary problems must be weighed against sexual side effects and the increased risk of high-grade prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
1,594
8
50

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,468 publications
(1,721 citation statements)
references
References 21 publications
52
1,594
8
50
Order By: Relevance
“…The hypothesis that finasteride shrinks existing tumors is supported by the observation that the rates of prostate cancer in men treated with finasteride and placebo diverged early in PCPT. 9 Although the model is unable to shed further light on this topic, it appears possible that using finasteride resulted in a mixture of primary prevention and prevention of tumor progression in PCPT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis that finasteride shrinks existing tumors is supported by the observation that the rates of prostate cancer in men treated with finasteride and placebo diverged early in PCPT. 9 Although the model is unable to shed further light on this topic, it appears possible that using finasteride resulted in a mixture of primary prevention and prevention of tumor progression in PCPT.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Dividing the detection rates from PCPT by these calculated true detection rates provided a detection probability, which was then applied to the model using average prostate volumes of 34 (placebo group) and 26 cc (finasteride group), representing median prostate volumes at the end of study biopsy. 9 Table 1 shows the minimum number of PZ and TZ biopsy cores needed for a 0.90 or greater probability of cancer detection for a total tumor volume of 1.0 and 3.0 cc by prostate volume. As would be expected, an increasing number of biopsies were required to ensure a probability of 0.90 or greater as prostate volume increased and tumor volume decreased.…”
Section: Modeling the Influence Of Prostate Volume And Tumor Size Redmentioning
confidence: 99%
See 1 more Smart Citation
“…One phase III study examining finasteride has been completed and results have shown a 25% reduction in the period prevalence of PCa over 7 years. 1 Although initially the development of high-grade PCa under finasteride treatment was viewed as a detrimental effect, 1 recently published new analyses demonstrated this to be an artifact, and in fact, these analyses suggest overall a 30% reduction in the period prevalence of PCa under finasteride with no increased risk for high-grade cancer. [2][3][4][5] Dutasteride 6 is also currently being evaluated in phase III placebo-controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a variety of studies, using various designs and testosterone formulations, over periods ranging from several months to 15 years, in men with a wide range of ages, have not revealed an increased risk of prostate cancer [139][140][141][142][143][144][145][146][147][148][149][150][151][152][153][154]. A meta-analysis found that testosterone treatment in older men compared to placebo was not associated with a significantly higher risk of detection of prostate cancer [131], although the frequency of prostate biopsies was much higher in the testosterone-treated group than in the placebo group [131].…”
Section: Lower Urinary Tract Symptoms and Prostate Diseasementioning
confidence: 97%